Augmented Reality for Assembly Training in Industry: A Systematic Literature Mapping - Cim, Vanessa S.; Hounsell, Marcelo Da Silva (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
Training as a basis for professional development contributes to the dissemination of knowledge in organizations. This Systematic Literature Mapping (SLM) aims to identify the approaches and instruments of corporate training for manual assembly with Augmented Reality (AR) in industries. The SLM was carried out in the ACM Digital Library and IEEE Xplore database with a total of 151 papers found and after applying the selection criteria, 28 papers were analyzed. We found that most systems were tested in simulated environment and not always assessed by users perspective. Task completion time and number of errors are two very frequent measurements. No theoretical pedagogical approach was found which suggests that the research is still focused on system´s design issues such as interface, information and graphics. Existing AR-based manual assembly training systems simply reproduce the intended task as a basis for training. The results show that AR supports the training process, but it is still in the development phase and it is necessary to investigate approaches that demonstrate the pedagogical practices used. The aspects of the AR-based learning processes are yet to be fully explored.